2020
DOI: 10.1371/journal.pone.0233809
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress reduces growth rate of red deer calf: Climate warming implications

Abstract: Climate models agree in predicting scenarios of global warming. In endothermic species heat stress takes place when they are upper their thermal neutral zone. Any physiological or behavioural mechanism to mitigate heat stress is at the cost of diverting energy from other physiological functions, with negative repercussions for individual fitness. Tolerance to heat stress differs between species, age classes and sexes, those with the highest metabolic rates being the most sensitive to stressing thermal environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…Considering that, over the study, hinds were fed equally and that protein concentration increased as a consequence of a milk concentration effect, this decrease in urea at the end of the lactation could be explained by a lower protein intake by hinds in these last weeks, coinciding with the hottest period during lactation. Studies on heat stress in hinds and calves at our farm have shown that increased heat stress leads to a lower growth in calves and, in the case of higher values of thermal stress indices, also in lactating females [ 36 ]. The literature on cattle shows feed intake reduction and lower protein in milk during high thermal stress in cows [ 37 ], but while the latter study showed no effect of heat stress on urea, Costa et al [ 38 ] showed in buffalo that urea had one of the strongest correlations with heat stress indices, although a positive one and not the postulated negative one of our results.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that, over the study, hinds were fed equally and that protein concentration increased as a consequence of a milk concentration effect, this decrease in urea at the end of the lactation could be explained by a lower protein intake by hinds in these last weeks, coinciding with the hottest period during lactation. Studies on heat stress in hinds and calves at our farm have shown that increased heat stress leads to a lower growth in calves and, in the case of higher values of thermal stress indices, also in lactating females [ 36 ]. The literature on cattle shows feed intake reduction and lower protein in milk during high thermal stress in cows [ 37 ], but while the latter study showed no effect of heat stress on urea, Costa et al [ 38 ] showed in buffalo that urea had one of the strongest correlations with heat stress indices, although a positive one and not the postulated negative one of our results.…”
Section: Resultsmentioning
confidence: 99%
“…A delay in conception date might produce a mismatch between actual births and optimal calving date, which may increase calf mortality [ 105 , 106 ]. Moreover, nutritional stress during pregnancy and lactation has been shown to affect calf body mass and immune system which are related to their future survival and reproductive success [ 97 , 104 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Climate models predict a rise in land surface temperature between 1 and 3.7°C for the period 2046–2100 [ 1 ], with direct negative consequences on livestock production, prevalence of diseases and parasites [ 2 ] and body growth [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of these methods has been measured using behavioural and metabolic proxies of animal heat stress, such as changes in behavioural activity, food intake, rectal temperature, metabolites and stress-related hormone concentrations (Bell et al, 1989 [ 13 ]; Dussault et al, 2004 [ 14 ]; López et al, 2018 [ 15 ]; Spiers et al, 2004 [ 16 ]; Correa-Calderon et al, 2004 [ 17 ]; Strickland et al, 1989 [ 68 ]; Turner et al, 1992 [ 11 ]), and assessing animal condition and production [ 6 , 18 ]. In polygynous species, such as red deer [ 19 – 21 ], males are larger than females from birth and their sexual dimorphism in body size increases with age [ 3 , 22 , 23 ]. Pérez-Barbería et al [ 3 ] hypothesised that calves of the most costly sex to produce, ie.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation